Teachers’ and Students’ Attitude Toward Code Alternation in Pakistani English Classrooms - Aqsa Tahir; Iqra Fatima; Namrah Abuzar (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2016)
This research is an attempt to explore students' and teachers‟ attitude towards code alternation within English classrooms in Pakistan. In a country like Pakistan where official language is English, the national language is Urdu, and every province has its own language, most of the people are bilinguals or multilingual. Therefore, the aim of this study was to find out when and why teachers code switch in L2 English classrooms. It has also explored student's preferences of language during learning second language. It has also looked into teachers' code-switching patterns and the students‟ priorities. Ten teachers responded to an open ended questioner and 100 students responded to a close ended questioner. Results of teacher's responses indicated that they mostly code switch when student's response in relation to the comprehensibility is negative and they do not grasp the concepts easily in L2. They never encourage students to speak Urdu. Student's results showed that they mostly prefer code-switching into their L1 for better understanding and participation in class. Analysis revealed that students only favored English while getting instructions of test, receiving results, and learning grammatical concepts. In most of the cases, students showed flexibility in language usage. Majority of students (68%) agreed upon that they learn better when their teachers code switch in to L1.